Pendampingan Pembuatan Media Buku Saku Untuk Pembelajaran Struktur Hewan - Kusmiyati; I Wayan Merta; Khairuddin (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
Learning media that are in accordance with the needs of learning activities will create effective and efficient learning activities. The purpose of this activity is to train students to compile interesting, concise, and easy-to-understand teaching materials in the form of pocket books. Mentoring is conducted to ensure that the products produced meet students' needs and contribute to the learning process. The design of the pocket book related to the covers made by each group is not restricted, all groups are welcome to explore their abilities, the content or number of pages made is also not restricted, the important thing is that all the materials that are their duties are summarized in the pocket book, The method used in this assistance is the discussion and question and answer method. The results of the assessment of pocket books made by students in terms of format, content, and language used showed that most of the groups were in the good category. It can be concluded that the creation of pocket books gives students experience in developing teaching materials that are interesting, concise, and easy to understand.